Asupot = . Asufot; ktav-et letoldot tenuat ha-avodah beam yisrael
Also titled Asufoth; from 1970 onward (new series) the title is slightly changed: Asupot, ktav-et le-toldot tnuat ha-avodah be-am Yisrael.